Introduction to reliability engineering - Lewis, E. E. (Elmer Eugene), 1938- (New York : John Wiley and Sons, 1999)
This book is about: Probability and sampling; Continuous random variables; Quality and its measures; ...
Keywords: Engineering; Reliability; Reliability (Engineering)